High-resolution trade-off analysis and optimization of ecosystem services and disservices in agricultural landscapes. (September 2018) - Nguyen, Trung H.; Cook, Maxwell; Field, John L.; Khuc, Quy V.; Paustian, Keith
Abstract: Agricultural land management often involves trade-offs between ecosystem services (ES) and disservices (EDS). Balancing these trade-offs to achieve low-impact production of agricultural commodities requires rigorous approaches for quantifying and optimizing ES and EDS, reconciling biophysical constraints and different management objectives. In this study, we demonstrate a high-resolution spatially-explicit analysis of ES and EDS trade-offs for irrigated corn production systems in the South Platte River Basin, Colorado, USA, as a case study. The analysis integrated a biogeochemical model (DayCent) with optimization algorithms to assess trade-offs between multiple ES and EDS indicators, including net primary production, soil organic carbon, water use, nitrogen leaching, and greenhouse gas emissions. Our results show a large fraction of total potential system productivity (up to 21 Mg ha −1 year −1 ) can be realized at minimal ecosystem impacts through careful land management decisions. Our analysis also explores how different land management objectives imply different landscape configurations. Highlights: High-resolution quantification of ecosystem services (ES) and disservices (EDS). Linkage between DayCent model with optimization algorithms for trade-off analysis. Results showed convex Pareto trade-off frontiers among ES and EDS. 90% of potential landscape production can be achieved at minimal ecosystem impacts. Optimum fertilizer and irrigation rates were identified on a field-by-field basis.